EFFECTIVENESS OF AXIAL RELEASE AND SUSTAINED MOBILIZATION ON SHOULDER ELEVATION IN INDIVIDUALS WITH ADHESIVE CAPSULITIS – A PROSPECTIVE AND COMPARATIVE STUDY - SUNIL G HARSULKAR; KARISHMA KAPUR; SACHIN SHETTI; SURYAVANSHI TEJAS V (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to investigate the comparative effectiveness of axial release and sustained mobilization on shoulder elevation in individuals with adhesive capsulitis. Methods: The present study recruited total 30 participants diagnosed as adhesive capsulitis as per the inclusion and exclusion criteria. They were allocated into Group A and Group B according to convenient sampling. Participants in Group A were treated with conventional physiotherapy, axial release, and sustained mobilization technique and Group B received Maitland mobilization with conventional physiotherapy. The interventions were given for 4 weeks, 3 sessions/week for 30 min. The outcome measures used in the study were numerical pain rating scale, shoulder pain and disability index, and universal goniometer which was assessed before the intervention immediately after the first session and at 2nd week and on completion of 4th week. Results: When the data statically analyzed intragroup group comparisons found to be significantly reduced in terms of pain and shoulder pain and disability index and improvement in Shoulder range of motion (p<0.05). Intergroup comparisons also showed significant difference in both the groups, but the results were more significant in Group A (p<0.05). Conclusion: Both interventions in the form of articular and soft-tissue mobilization should be incorporated in the management of adhesive capsulitis.